THE POSSIBILITY OF PREDICTING THE OUTCOMES OF ORGAN-PRESERVING INTERVENTIONS FOR UTERINE FIBROIDS - E. V. Bashirov; V. A. Krutova; T. G. Melkonyanc (Медицинский вестник Юга России, 2016)
Purpose: to evaluate the impact of a comprehensive rehabilitation therapy on the results of organ-preserving UF treatment technology being based on the study of adaptation reactions nature and cytokine profile. Materials and methods: the study involved 265 women with uterine fibroids after laparoscopic myomectomy, laparotomic myomectomy and UAE (with and without complex rehabilitation after surgery). Adaptation reactions after different treatment technologies and cytokine profile after UAE (TNF-α, IL-1β, IL-2, IL-6, IL-4, IFN-γ, Fas-L) were under thorough study. Results: myoma growth relapses during the observation period were distinguished among 12 patients after LSM, 16 – after LTM, 11 – after UAE. Molecular mechanisms of disease recurrence were clarified, especially in the absence of rehabilitation: long-term proinflammatory shift characteristic of an early postoperative period, destructive processes aggravation in the injured myometrial tissue with the increase in the dynamics of anti-apoptotic activity (Fas-L lack), Th1-cell factors depletion and immunosuppression development. Summary: the profile of adaptation reactions is shown to be not only the predictor of disease recurrence but also the criterion of a full-course rehabilitation. Cytokine profile study after UAE contributes to the prediction of treatment technology ineffectiveness.